Makna Persahabatan Sebuah Tinjauan Dari Perspektif Filsafat - Justinus Sudarminta (Seri Filsafat Teologi, 2020)
This article is meant to be a philosophical reflection on the meaning of friendship. As evident from its sub-titles, the article is divided into four parts. First, it deals with the notion of friendship, in which the genuine friendship, or in Aristotle’s term called the perfect form of friendship, is distinguished from the egoistic or the imperfect forms. Referring to Aristotle’s account of friendship, the perfect form of friendship is a friendship in which each friend values the other for their own particular qualities, for their own sake, for their virtuous character and not for the pleasure or utilities they can provide. The imperfect forms of friendship usually do not last long, because the tie of friendship will get loose and finally dissolved when it does not bring either pleasure or utilities each friend wants. Second, following Aristotle, I try to explain why friendship is considered important for human happiness. Third, the element of right and duty that get involved in the personal relation of friendship is being addressed. Finally, due to the increasing importance of online communication nowadays, especially during this pandemic corona virus outbreak, I would like also to address the opportunities and challenges of online friendship or the relation of friendship mediated by social media. In this regard, the opportunity to foster online friendship is bigger under the model of moral friendship according to Kant and Kierkegaard in which universal love is emphasized, and Nietzsche’s model in which the agonistic nature of friendship is highly valued, than under the Aristotle’s model.